J'ai besoin d'un coup de main merci :)

Dévellopper puis réduire si possible:

A= (x+4) (x-6) + (-1+x) (x+7)
B= ( x-1 ) (5x - 2) - ( -6+3x (-1+x)
C= - (3x-8) (x+4) - (7x-8) (-1+7x)
D= - (2x-5) (3-4x) + (6x-9) (-2x-1)

1

Réponses

2014-01-28T15:08:03+01:00
Bonjour

A= (x+4) (x-6) + (-1+x) (x+7) = x² -x +4x -24 -x -7 +x² +7x = 2x²  +9x -31
B= ( x-1 ) (5x - 2) - ( -6+3x (-1+x) = 5x² -2x -5x +2 - (6 -6x -3x +3x²) = 5x² -7x +2 -6 +6x +3x -3x² = 2x² +2x -4
C= - (3x-8) (x+4) - (7x-8) (-1+7x) = 3x² +12x -8x -32 - ( -7x +49x² +8 - 56x) = 3x² + 4x -32 +7x -49x² -8 +56x = - 46x² +67x -40
D= - (2x-5) (3-4x) + (6x-9)  (-2x-1)
= - (6x - 8x² -15 + 20x -12x² - 6x +18x +9) = 20x² -38x +9